2021
DOI: 10.1038/s41598-021-87740-8
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis sativa terpenes are cannabimimetic and selectively enhance cannabinoid activity

Abstract: Limited evidence has suggested that terpenes found in Cannabis sativa are analgesic, and could produce an “entourage effect” whereby they modulate cannabinoids to result in improved outcomes. However this hypothesis is controversial, with limited evidence. We thus investigated Cannabis sativa terpenes alone and with the cannabinoid agonist WIN55,212 using in vitro and in vivo approaches. We found that the terpenes α-humulene, geraniol, linalool, and β-pinene produced cannabinoid tetrad behaviors in mice, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 46 publications
5
70
2
Order By: Relevance
“…Cannabis plants have attracted much attention for medical uses due to the importance of secondary metabolites, for which demand increased in the last decade following the discovery of the main compound present in Cannabis sativa — cannabinoids. Cannabinoids, a class of compounds specific to cannabis, are responsible for the vast majority of its medicinal activity (Gaoni and Mechoulam, 1964 ; Gorelick and Bernstein, 2017 ; Freeman, et al, 2019 ; Nelson, et al, 2020 ; LaVigne, et al, 2021 ). Here, we will simplify the potential of microbes for cannabinoid production, and how they could be manipulated for the stabilization of biosynthesis of different cannabinoids.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis plants have attracted much attention for medical uses due to the importance of secondary metabolites, for which demand increased in the last decade following the discovery of the main compound present in Cannabis sativa — cannabinoids. Cannabinoids, a class of compounds specific to cannabis, are responsible for the vast majority of its medicinal activity (Gaoni and Mechoulam, 1964 ; Gorelick and Bernstein, 2017 ; Freeman, et al, 2019 ; Nelson, et al, 2020 ; LaVigne, et al, 2021 ). Here, we will simplify the potential of microbes for cannabinoid production, and how they could be manipulated for the stabilization of biosynthesis of different cannabinoids.…”
Section: Introductionmentioning
confidence: 99%
“…Radioligand binding was generally carried out as reported in our previous work (e.g., [15,[27][28][29]). Briefly, 30 µg of cell membrane protein was combined with 0.89 nM of 3 Hdiprenorphine (PerkinElmer, #NET1121250UC) and concentration curves of experimental ligand or reference drug (see Figure Legends for details) in a 200 µL reaction volume.…”
Section: Competition Radioligand Bindingmentioning
confidence: 99%
“…Two recent studies have demonstrated a lack of interaction among common terpenoids on CB 1 receptors [ 13 , 14 ] but without accounting for other mechanisms of action that might produce such synergy, whether by boosting therapeutic effects or reducing adverse events attributable to THC [ 2 ]. A recent study did show cannabimimetic effects by common cannabis terpenoids [ 15 ] but at concentrations at or above 100 µM. It is highly likely that consumers distinguish differences in the subjective experience that they experience from different cannabis chemovars [ 9 ].…”
Section: Discussionmentioning
confidence: 99%